SOLUTION
We use the method of separation of variables. We are looking for a solution in the form:
"u(x,n)=X(x)N(n)" Then,
"\\left\\{\\begin{array}{c}\nu_n=\\displaystyle\\frac{\\partial}{\\partial n}\\left(X(x)N(n)\\right)=X(x)N'(n)\\\\[0.5cm]\nu_{xx}=\\displaystyle\\frac{\\partial^2}{\\partial x^2}\\left(X(x)N(n)\\right)=X''(x)N(n)\n\\end{array}\\right.\\longrightarrow"
"u_n=u_{xx}\\,\\,\\,equivalent\\,\\,\\,\\\\[0.3cm]\nX(x)N'(n)=X''(x)N(n)\\left|\\cdot\\frac{1}{X(x)N(n)}\\right."
"\\frac{N'(n)}{N(n)}=\\frac{X''(x)}{X(x)}=-\\lambda" We arrive at the Sturm-Liouville problem
"\\left\\{\\begin{array}{c}\nX''(x)+\\lambda X(x)=0\\\\[0.3cm]\nX(0)=X(l)=0\n\\end{array}\\right." We are looking for a solution in the form
"X(x)=e^{kx}\\rightarrow X''(x)=k^2\\cdot e^{kx}"
"X''(x)+\\lambda X(x)=0\\rightarrow k^2\\cdot e^{kx}+\\lambda\\cdot e^{kx}=0\\rightarrow"
"e^{kx}\\left(k^2+\\lambda\\right)=0\\rightarrow k^2=-\\lambda\\rightarrow\\\\[0.3cm]\n\\left[\\begin{array}{c}\nk_1=\\sqrt{-\\lambda}=i\\sqrt{\\lambda}\\\\[0.3cm]\nk_2=-\\sqrt{-\\lambda}=-i\\sqrt{\\lambda}\n\\end{array}\\right." Conclusion,
"X(x)=C_1e^{ix\\sqrt{\\lambda}}+C_2e^{-ix\\sqrt{\\lambda}}\\\\[0.3cm]\nor\\\\[0.3cm]\nX(x)=A\\cos\\left(x\\sqrt{\\lambda}\\right)+B\\sin\\left(x\\sqrt{\\lambda}\\right)" We use the boundary conditions
"X(0)=0=A\\cos\\left(0\\sqrt{\\lambda}\\right)+B\\sin\\left(0\\sqrt{\\lambda}\\right)\\\\[0.2cm]\n\\boxed{A=0}\\\\[0.2cm]\nX(l)=0=B\\sin\\left(l\\sqrt{\\lambda}\\right)\\rightarrow \\sin\\left(l\\sqrt{\\lambda}\\right)=0\\\\[0.2cm]\nl\\sqrt{\\lambda}=k\\pi,\\,\\,\\,k=1,2,3,\\ldots\\\\[0.2cm]\n\\lambda_k=\\left(\\frac{k\\pi}{l}\\right)^2,\\,\\,\\,k=1,2,3,\\ldots" Conclusion,
"\\left\\{\\begin{array}{c}\nX_k(x)=B_k\\sin\\left(\\displaystyle\\frac{xk\\pi}{l}\\right)\\\\[0.3cm]\n\\lambda_k=\\left(\\displaystyle\\frac{k\\pi}{l}\\right)^2,\\,\\,\\,k=1,2,3,\\ldots\n\\end{array}\\right." Then,
"\\frac{N'(n)}{N(n)}=-\\lambda_k\\rightarrow\\frac{dN(n)}{N(n)}=-\\lambda_kdn\\rightarrow\\\\[0.3cm]\n\\boxed{N_k(n)=e^{-\\lambda_kn}}" Conclusion,
The particular solution has the form
"u_k(x,n)=X_k(x)N_k(n)=B_k\\sin\\left(\\displaystyle\\frac{xk\\pi}{l}\\right)e^{-\\lambda_kn}" General solution is
"u(x,n)=\\sum_{k=1}^\\infty u_k(x,n)=\\sum_{k=1}^\\infty B_k\\sin\\left(\\displaystyle\\frac{xk\\pi}{l}\\right)e^{-\\lambda_kn}" It remains to determine the constants "B_k" , for this we use the initial condition
"u(x,0)=x(l-x)=\\sum_{k=1}^\\infty B_k\\sin\\left(\\displaystyle\\frac{xk\\pi}{l}\\right)\\\\[0.3cm]\n\\int_0^l\\left(x(l-x)\\sin\\left(\\displaystyle\\frac{xm\\pi}{l}\\right)\\right)dx=\\\\[0.3cm]\n=\\sum_{k=1}^\\infty B_k\\int_0^l\\sin\\left(\\displaystyle\\frac{xm\\pi}{l}\\right)\\sin\\left(\\displaystyle\\frac{xk\\pi}{l}\\right)dx\\\\[0.3cm]\nB_m\\frac{l}{2}=I_1+I_2" where
"I_1=l\\int_0^l\\left(x\\sin\\left(\\displaystyle\\frac{xm\\pi}{l}\\right)\\right)dx=-(-1)^m\\frac{l^3}{m\\pi}\\\\[0.3cm]\nI_2=-\\int_0^l\\left(x^2\\sin\\left(\\displaystyle\\frac{xm\\pi}{l}\\right)\\right)dx=\n\\frac{l^3(2-(2-m^2\\pi^2)(-1)^m)}{m^3\\pi^3}\\\\[0.3cm]\nI_1+I_2=-(-1)^m\\frac{l^3}{m\\pi}+\\frac{l^3(2-(2-m^2\\pi^2)(-1)^m)}{m^3\\pi^3}=\\\\[0.3cm]\n=\\frac{l^3(2-(2-m^2\\pi^2)(-1)^m)-m^2\\pi^2(-1)^m)}{m^3\\pi^3}=\\\\[0.3cm]\n=\\frac{l^3(2-2\\cdot(-1)^m)}{m^3\\pi^3}=\\frac{2l^3(1-(-1)^m)}{m^3\\pi^3}" Then,
"B_m\\frac{l}{2}=\\frac{2l^3(1-(-1)^m)}{m^3\\pi^3}\\rightarrow\n\\boxed{B_m=\\frac{4l^2(1-(-1)^m)}{m^3\\pi^3}}" Conclusion,
"u(x,n)=\\sum_{k=1}^\\infty \\frac{4l^2(1-(-1)^k)}{k^3\\pi^3}\\sin\\left(\\displaystyle\\frac{xk\\pi}{l}\\right)e^{-\\lambda_kn}" ANSWER
"u(x,n)=\\sum_{k=1}^\\infty \\frac{4l^2(1-(-1)^k)}{k^3\\pi^3}\\sin\\left(\\displaystyle\\frac{xk\\pi}{l}\\right)e^{-\\lambda_kn}\\\\[0.3cm]\n\\lambda_k=\\left(\\frac{k\\pi}{l}\\right)^2,\\,\\,\\,k=1,2,3,\\ldots"
Comments
Leave a comment